Load Balancing Using The Consensus Control Algorithm For A Network Server System - Loon, Alan Tan Chin (2016)

(untitled)
An internet datacenter is an apt example of a distributed network with dynamic loads, and a load balancing algorithm is needed in a datacenter to manage and distribute the loading to all server nodes appropriately. The implementation of a load balancer brings benefits to both the datacenter owner and Cloud users as it prolongs the lifespan of servers and improve the quality of service. An average consensus algorithm using PID control is proposed for the implementation in a network of server nodes and the result is compared to an existing model. The proposed algorithm is simulated with different number of nodes and edges. Furthermore, the designed load balancer is subjected to different graph topologies to test its adaptability. The performance results are found to be better than the existing model using PI.